2015
DOI: 10.1044/2014_jslhr-l-14-0174
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a General Auditory Processing Deficit in Developmental Dyslexia From a Discrimination Paradigm Using Speech Versus Nonspeech Sounds Matched in Complexity

Abstract: These results support the existence of a general auditory processing impairment in developmental dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 103 publications
2
13
0
1
Order By: Relevance
“…In most cases, however, if one of those three dimensions was affected, the deficit co-occurred with at least one other, or even all deficits. Christmann et al (2015) found similar results for adult dyslexics with respect to temporal, spectral, or spectrotemporal deficits.…”
Section: Comorbidities and Predictors Of Developmental Dyslexia And Dsupporting
confidence: 62%
“…In most cases, however, if one of those three dimensions was affected, the deficit co-occurred with at least one other, or even all deficits. Christmann et al (2015) found similar results for adult dyslexics with respect to temporal, spectral, or spectrotemporal deficits.…”
Section: Comorbidities and Predictors Of Developmental Dyslexia And Dsupporting
confidence: 62%
“…Accordingly, it has been suggested that general auditory processing difficulties may underlie phonological processing weaknesses in those with dyslexia (as reviewed in Goswami, 2011 ; Hamalainen et al, 2013 ; Goswami, 2015 ). However, not all children with dyslexia show deficits in auditory processing ( Nittrouer, 1999 ; Marshall et al, 2001 ; Ramus, 2003 ; Rosen, 2003 ; Grube et al, 2014 ; Steinbrink et al, 2014 ; Christmann et al, 2015 ). Therefore, a multiple deficit view of dyslexia, in which deficits in basic auditory processing may be one of several factors that give rise to difficulties with learning to read, offers a promising perspective that accounts for the complex nature of reading acquisition ( Pennington, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that relatively minor deficiencies in low-level auditory (cf. Ahissar, Protopapas, Reid, & Merzenich, 2000;Christmann, Lachmann, & Steinbrink, 2015;Hämäläinen, Salminen, & Leppänen, 2013;Richardson, Thomson, Scott, & Goswami, 2004;Talcott & Witton, 2002) and low-level visual (cf. Becker, Elliott, & Lachmann, 2005;Slaghuis & Ryan, 1999;Stein, 2002;Stein & Talcott, 1999) abilities result in suboptimal reading routines.…”
Section: Reading Level Control Groupsmentioning
confidence: 99%